Long-term plasma exchange as maintenance therapy for cerebellar-type Hashimoto's encephalopathy, a case report. Issue 3 (June 2018) - Tran, Minh-Ha; Mkhikian, Haik; Sy, Michael; Perez-Alvarez, Ingrid; Demetriou, Michael
Abstract: Hashimoto's encephalopathy (HE) is a presumed autoimmune disorder associated with anti-thyroid autoantibodies and signs and symptoms of encephalopathy. A sub-type of HE is associated with cerebellar dysfunction and ataxia. Immunosuppressive therapy, particularly corticosteroid treatment, is utilized in the majority of cases. Short-term apheresis has been reported with variable patient responses. Here we report the case of a 72 year-old female with an ∼15 year history of cerebellar type HE that had profound improvement in symptoms after long-term apheresis treatment over an ∼2 year period. Following an induction phase, twice-weekly maintenance apheresis of 1 plasma volume reversed long-standing severe gait ataxia that had required a walker, as well as mild cognitive symptoms. This paralleled reductions in anti-thyroid antibody levels. Holidays from apheresis lasting several weeks and/or reductions in maintenance apheresis frequency to once per-week resulted in re-expression of ataxia and cognitive impairments along with a rise in anti-thyroid antibody levels. An apheresis dose-effect was observed whereby parallel rise and fall in both symptomatology and antibody levels would mirror duration between apheresis intervals. To our knowledge, this is the first report of profound therapeutic benefit and a dose-response relationship to long-term apheresis in cerebellar-type HE. This case suggests that maintenance apheresis be considered in responsive patients, particularly in those with contraindications to medical immunosuppression.